Synthetic aperture in controlled source electromagnetic for the monitoring and exploration of reservoirs on land (2018)
Abstract: The following doctoral thesis is composed of five scientific papers, structured in three chapters. Three of these papers are already published in international journals, and two are currently under review. According to the stated objectives in this work, these chapters are grouped into two general sections, namely: Section I. Golden zone of sedimentary basins in the Colombian territory; Section II. Exploration of reservoirs on land using electromagnetic methods.